ESTUDO ANATÔMICO DO CANAL RADICULAR DE DENTES DE Cebus apella - Rafael Rodrigues Lima; Leila Marques Araújo; Priscilla Rocha Afonso; Suely Maria Lamarão (Ciência Animal Brasileira, 2008)
An anatomic study of Cebus apella root teeth was performed to analyze the internal anatomy of permanent dentition, normalizing its use as experimental model endodontic research. Twelve adult animals were used in this study. After the removal of the organic tissue, the all teeth were removed, sectioned, analyzed and photographed with a stereomicroscope. The results showed that the anatomy of root canal of this species are similar to human dental anatomy, considering the shape, pathway and number of canals, but with some peculiarities, such as: the root canal anatomy varied from oval to circular; in the lower canines, the canals are resembled a kidney, reflecting the outside contour of the root; in the upper molars, the mesiobuccal and distobuccal canals are oval, following the general contour of the tooth. The authors conclude that this primate can be applied as models for study of root canal treatment in human beings, in special the upper central and lateral incisors, upper and lower canines and first, second, third lower premolars present single and wide canal with easy access being ideals for endodontic experiments.